2007
DOI: 10.1016/j.cmet.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PKCɛ Improves Glucose-Stimulated Insulin Secretion and Reduces Insulin Clearance

Abstract: In type 2 diabetes, pancreatic beta cells fail to secrete sufficient insulin to overcome peripheral insulin resistance. Intracellular lipid accumulation contributes to beta cell failure through poorly defined mechanisms. Here we report a role for the lipid-regulated protein kinase C isoform PKCepsilon in beta cell dysfunction. Deletion of PKCepsilon augmented insulin secretion and prevented glucose intolerance in fat-fed mice. Importantly, a PKCepsilon-inhibitory peptide improved insulin availability and gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
118
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(137 citation statements)
references
References 46 publications
15
118
4
Order By: Relevance
“…Additional supportive evidence is the amelioration of the glucose uptake in cells treated with both oleate and the Bis-I, but not in cells treated with palmitate. PKC activation has been implicated in several studies of insulin resistance and diabetes and even in the absence of lipid oversupply [11,25,26]. The inhibitory effects of PKC on insulin signaling may at least in part be explained by the more recently identified role of the serine/ threonine phosphorylation of IRS-1, which has been implicated in the inhibition of its tyrosine phosphorylation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Additional supportive evidence is the amelioration of the glucose uptake in cells treated with both oleate and the Bis-I, but not in cells treated with palmitate. PKC activation has been implicated in several studies of insulin resistance and diabetes and even in the absence of lipid oversupply [11,25,26]. The inhibitory effects of PKC on insulin signaling may at least in part be explained by the more recently identified role of the serine/ threonine phosphorylation of IRS-1, which has been implicated in the inhibition of its tyrosine phosphorylation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The data show that the beta cell decompensation phase and glucolipotoxicity are associated with beta cell exhaustion, a specific reduction in GSIS, and there is some evidence of mild beta cell 'dedifferentiation'. We propose that the chronic accumulation of diacylglycerol (DAG) contributes to cause reduced GSIS via sustained activation of some PKC isoforms, in particular PKC epsilon, the inhibition of which improves GSIS [41]. The figure also shows that many factors that have been proposed to be causally linked to beta cell failure, in particular a falling beta cell mass, beta cell steatosis and reduced glucose metabolism, do not explain the beta cell demise in this animal model of mild to moderate type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diacylglycerol activates protein kinase C (PKC) enzymes and chronic activation of beta cell PKC with phorbol esters suppresses GSIS. In addition, the diacylglycerol-sensitive PKC epsilon plays an inhibitory role in GSIS [41]. Thus, it can be hypothesised that the reduced GSIS in ZF-Px islets may in part be due to chronic activation of specific PKC enzyme(s) as a result of diacylglycerol deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of PKC isoform-selective knock-out mice have indicated important roles for PKCδ and -λ in insulin secretion (Hashimoto et al, 2005;Uchida et al, 2007). Deletion of PKCε did not affect normal glucose-induced insulin secretion, but amplified that in islets treated with fatty acids (Schmitz-Peiffer et al, 2007). However, another study showed that expression of a dominant negative mutant of PKCε suppressed insulin exocytosis in isolated β-cells (Mendez et al, 2003).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 99%